A study of functional outcome of distal femur fractures internally fixed with distal femur locking compression plate - Singh, Sardar Jaideep; Sree, K. Usha; Srinivas, Shanmukha; Pasula, Sujatha (ScienceRise: Medical Science, 2022)
The femur is the largest bone in the body connecting between the tibia and pelvic bone. Studies have proved this bimodal distribution of supracondylar fractures of the femur. The locking plate's standard is to have an anatomical reduction of the bone under the soft tissue envelope and could be applied without stripping the periosteum. The aim: to study the union rates with locking compression plates and clinical outcome associated with this treatment modality, range of movements of the knee, pain relief and return to normal activities and work. Methodology: this is a prospective study on patients with distal femur fractures. Conducted at Santhiram medical college and general hospital, Nandyal from October 2018 to September 2020. All patients aged more than 18 years diagnosed with distal femur fractures. Results: in our study, around 46 % of them had Muller A1 type, followed by 23 % had Muller C1 and C2 respectively, and the remaining 13.3 % had Muller A2. Around 67 % had a Thomas splint with traction, 16.7 % had B.B. splint, 13.3 % had A/K POP slab, and the remaining 3 % had upper tibial traction with B.B. splint. The majority of the study participants, 53 %, had knee flexion more than 120 degrees. 30 %, took <16 weeks for the union, 33 %, took 16-20 weeks to complete weight-bearing, eight patients (26 %) had excellent outcomes; 21 patients (70 %) had a satisfactory outcome; one patient (3.3 %) had an unsatisfactory outcome. Conclusion: in our study, out of 30 patients, eight patients had excellent outcomes, 21 patients had satisfactory outcomes, and one patient had unsatisfactory outcomes. We conclude, open reduction and internal fixation with a locking compression plate resulted in good clinical and radiologic outcomes